An Experimental Study To Analysis The Effect Of Scar Rehabilitation Along With Core Strengthening Exercises In Patient With Low Back Pain - Puri, Ojha Akansha; Khan, Jafar; Warsi, Rahat khan; Sharma, Deepak; Pal, Renuka; Annamalai, KM.; Jain, Vardhman; Dubey, Sudhir; Joshi, Jayesh; Menaria, Dinesh (Journal of Neonatal Surgery, 2025)
Background:Low back pain (LBP) is a leading global cause of disability and often persists despite conventional treatment. In post-surgical populations, such as women after cesarean section, scar tissue has been proposed as a potential contributor to chronic LBP. However, the impact of targeted scar rehabilitation in conjunction with core strengthening remains underexplored. Objective:To evaluate the effect of combining scar rehabilitation techniques with core strengthening exercises on pain intensity and functional disability in individuals with chronic low back pain. Methods:A total of 60 participants with nonspecific low back pain were divided into two groups: one receiving conventional core strengthening exercises and the other receiving a combination of scar rehabilitation and core strengthening. Pain intensity and functional disability were assessed using the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) respectively, pre- and post-intervention. Data were statistically analyzed using paired and independent t-tests, and chi-square tests where appropriate. Results:Both groups showed significant improvement in pain and disability scores. However, the group receiving scar rehabilitation plus core strengthening exhibited superior outcomes. VAS scores reduced from 5.79 ± 2.13 to 0.79 ± 0.77 (p < 0.001), and ODI scores dropped from 0.45 ± 0.16 to 0.04 ± 0.05 (p < 0.001). Improvements were consistent across sex, pain side, and duration subgroups. Conclusion:The integration of scar rehabilitation with core strengthening provides greater benefits than core strengthening alone in reducing pain and disability among chronic LBP patients, especially those with a history of abdominal surgery. These findings highlight the importance of addressing scar tissue dysfunction in musculoskeletal rehabilitation